SISTEM INFORMASI PENGELOLA ADMINISTRASI KEARSIPAN BERBASIS WEB PADA MTI IBRAHIMY SUKOREJO - Moh. Labib Hammam Furqony; Abdus Samad (Jurnal Riset Sistem Informasi, 2025)
The rapid development of information technology has brought a significant impact on administrative management, particularly in the field of education. Web-based information systems function not only as a medium for presenting data but also as an interactive tool that supports decision-making processes. However, document archiving at MTI Ibrahimy Sukorejo is still carried out manually using agenda books and physical storage, which often leads to issues such as document loss, duplication, and difficulties in retrieving older records. This study was conducted through a Field Work Practice (PKL) using observation and interviews with the administrative office of MTI Ibrahimy Sukorejo. The objective is to design a web-based archival information system to support the recording of incoming letters, outgoing letters, and diplomas. The system was developed using the waterfall model, consisting of requirement analysis, design, implementation, and testing. The results indicate that the system can accelerate data processing, simplify document retrieval, and reduce the risk of record loss. Thus, it is expected to enhance administrative efficiency and provide tangible benefits for educational institutions